Dukungan Sosial Hubungannya dengan Kejadian Depresi pada Ibu yang Mempunyai Anak Gangguan Hiperkinetik - Anisa Renang Yulianti Soewadi Sumarni DW (Berita Kedokteran Masyarakat (BKM), 2011)
Beckground: Depression will be occurred in mothers who have children with hyperkinetic disorder with symptoms of inattention, hyperactivity, impulsivity, and also having difficulty to obey the regulation. Depression makes mothers felt into failure in taking care of their children. Having sadness and hopless in a long time leads them will fall into depression. They will need a physic, spiritual, and emotional rehabilitation. Therefore, a social supports is needed to encounter the problem. The social support can be given emotionally (attention or empa- thy), practically, and financial (money). An informative support can also reduce their problem. In contrast, the lack of support will cause them to be depressed.Objective: The objective of this research is to identify the correlation between social support and depression of mothers having children with hyperkinetic disorder in Arogya Mitra Clinic Klaten.Method: The method used in this research is cross-sectional study using descriptive analytic. The research is conducted in Arogya Mitra Clinic Klaten in March - April 2010. The sample is all of the population that the mothers having children with hiperkinetic disorder. The instruments used in the study are private data questionnaire, Sarason’s Social Support Questionnaire, and Montgomery-Asberg Depression Rating Scale. The data is ana-lyzed by using linier regression analysis.Result and Conclusions: According too the research frequency of depression of mothers having children with hyperkinetic disorder at Arogya Mitra Clinic is 31%. There are significant correlation between social support and depression of mothers having children with hyperkinetic disorder at Arogya Mitra Clinic (p<0,005) is 0,001.Keywords: social support, depression, mother, hyperkinetic disorder